2018
DOI: 10.1088/1758-5090/aac70b
|View full text |Cite
|
Sign up to set email alerts
|

Pre-set extrusion bioprinting for multiscale heterogeneous tissue structure fabrication

Abstract: Recent advances in three-dimensional bioprinting technology have led to various attempts in fabricating human tissue-like structures. However, current bioprinting technologies have limitations for creating native tissue-like structures. To resolve these issues, we developed a new pre-set extrusion bioprinting technique that can create heterogeneous, multicellular, and multimaterial structures simultaneously. The key to this ability lies in the use of a precursor cartridge that can stably preserve a multimateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 28 publications
(38 reference statements)
0
55
0
Order By: Relevance
“…We previously reported that the preset extrusion bioprinting technique could create heterogeneous, multicellular, and multimaterial structures simultaneously, depending on the design of the preset cartridge. [ 15 ] In this study, we designed and fabricated a new preset cartridge that resembles the structure of a human hepatic lobule ( Figure ). A hepatic lobule is a building block of the liver parenchyma, which is composed of hepatocytes arranged in the liver cords within a sinusoid network and a central vein.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that the preset extrusion bioprinting technique could create heterogeneous, multicellular, and multimaterial structures simultaneously, depending on the design of the preset cartridge. [ 15 ] In this study, we designed and fabricated a new preset cartridge that resembles the structure of a human hepatic lobule ( Figure ). A hepatic lobule is a building block of the liver parenchyma, which is composed of hepatocytes arranged in the liver cords within a sinusoid network and a central vein.…”
Section: Resultsmentioning
confidence: 99%
“…C) Free‐form endothelialized vessels can be obtained via printing with sacrificial gels and further studied to understand angiogenic sprouting in 3D. Reproduced under the terms of the Creative Commons CC‐BY 3.0 License ( https://creativecommons.org/licenses/by/3.0/) . Copyright 2018, The Authors, published by IOPScience.…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
“…Recently, an elegant alternative has been developed to use extrusion technologies to load spatially organized patterns of multiple cell types and microscale vascular structures within a single filament. Instead of coordinating the flow of multiple bioinks from different reservoirs into the printing nozzle, a single, multicompartment cartridge was developed to lodge more than one bioink . As during printing these inks are extruded in parallel from the same nozzle, the produced filament is templated by the geometry and loading pattern in the cartridge.…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
See 2 more Smart Citations